Pengaruh Waktu Fermentasi Pada Produksi Bioethanol Dari Molase - rahayu artini yuan (Universitas Muhammadiyah Surabaya, 2023)
The corona virus outbreak first occurred at the end of 2019 in Wuhan, China. This virus then spread rapidly throughout the world, including Indonesia. So, countries in the world take steps to lock down. In Indonesia, large-scale social restrictions have been implemented in big cities with a high prevalence of the spread of the virus. Efforts to control the virus include limiting mobility, wearing masks, frequently washing hands or using hand sanitizers. Hand sanitizers are products made from ethanol which are increasingly limited and expensive during the Covid-19 pandemic. The purpose of this study is to make bioethanol with a variation of the fermentation time made from molasses, so as to produce ethanol content above 70%. This research is an experimental research. Production of bioethanol based on molasses, aquades, NPK, urea, and yeast culture of Saccharomycess cerevisae with time variations of 4, 5, and 6 days and distilled at a temperature of 500C. Testing the ethanol content using gas chromatography mass spectrometry. The results of this study, the fourth day of fermentation produces ethanol content of 50.23±0.42% with an average volume of 490 mL; day 5 produced ethanol content of 62.92±0.38% with an average volume of 385 mL; and the 6th day yielded ethanol content of 72.11±0.46% with an average volume of 243 mL. So, the 6th day of fermentation is the best fermentation to produce bioethanol as a raw material for hand sanitizer with ethanol content above 70%.